Development of a Moderation-Based Islamic Education Learning Model in Efforts to Strengthen Student Tolerance at Public Universities in Lampung and Banten Provinces - Imam Syafei,; Wasehudin,; M. Asy'ari,; Rofiqi,; Cicik Aini, (TADRIS: Jurnal Pendidikan Islam, 2022)
The Indonesian nation is a large nation that has very diverse ethnic groups, races, cultures, and religions. This diversity will be very dangerous if it is not addressed properly by its adherents. Conflicts of religion, ethnicity, become something that cannot be avoided when every society does not have a strong attitude of tolerance. Islamic education as an educational system has a moral responsibility in order to form a moderate society in an effort to strengthen the tolerance attitude of students through the learning model that it provides. This study seeks to uncover and analyze the development of Islamic education based on religious moderation in an effort to strengthen student tolerance in public universities in the provinces of Lampung and Banten. The research method used in this study is research and development design, namely research used to produce certain products and test the effectiveness of these products. The results of this study indicate that moderation-based PAI learning has a major role in the formation of student tolerance attitudes in public universities in the provinces of Lampung and Banten. PAI learning based on religious moderation has a strong commitment to instilling multicultural values ​​into students so that they can respect the appeasement that occurs in the community. The results of the Development of Islamic Religious Moderation-Based Learning Model for students show that the PAI learning model can significantly increase students' religious tolerance. Therefore, the development of this learning model is highly recommended to be applied in the context of public universities, especially in the provinces of Lampung and Banten because they have a strong contribution to produce students who have a high tolerance attitude.